Analysis of the Efficiency of Shell and Tube, and Spiral Heat Exchangers - BINTI ABDUL LATIFF, NURUL HAFIZAH; BIN SEIS, Ir. Ts. Dr. MOHAMAD FARID (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Population growth, industrialization, and urbanisation have all contributed to a large increase in energy consumption, mostly from fossil fuels, which accounted for more than 80% of total energy supply between 2000 and 2018. This study looks at how heat exchangers, which are used in power production, manufacturing, and HVAC systems, might help enhance energy efficiency. The study seeks to improve the efficiency and performance of shell and tube and spiral heat exchangers by looking at their design and operational issues. Methodologically, the study entails developing a problem statement, examining literature, selecting models, and performing tests to determine heat transfer efficiency, Logarithmic Mean Temperature Difference (LMTD), and heat transfer coefficient. Results show that spiral heat exchangers outperform shell and tube ones in terms of heat transfer coefficient, demonstrating higher LMTD values and higher heat transfer rates, making them more suitable for educational and practical applications. The study helps to improve energy efficiency and sustainability, boosts industrial competitiveness by addressing maintenance and productivity issues, and broadens the knowledge base in thermal engineering, ultimately assisting in the development of more efficient and sustainable thermal solutions across various sectors.